The Influence of Workload and Organizational Culture on the Performance of Assembly Department Employees PT. Sakae Riken Indonesia - Eka Permata Sari; Suroso Suroso; Flora Patricia Anggela (Publikasi Indonesia, 2025)
PT Sakae Riken Indonesia’s Assembly Department faces performance challenges due to employees’ difficulty in adapting to workload demands and a Japanese-style organizational culture that emphasizes efficiency and Kaizen. This study investigates how these factors influence employee performance. The research aims to analyze (1) the partial effect of workload, (2) the partial effect of organizational culture, and (3) their simultaneous impact on employee performance. A quantitative approach was employed, using saturated sampling (43 employees) and questionnaires analyzed via SPSS 26. Multiple linear regression was used to test hypotheses, with validity, reliability, and classical assumption tests ensuring robustness. Workload (sig. 0.003, t=3.144) and organizational culture (sig. 0.000, t=4.353) significantly improved performance individually, while together they explained 65% of performance variance (F=14.613, sig. 0.000). The study highlights the need for balanced workload management and cultural adaptation support, offering practical insights for automotive firms. Future research should explore mediating variables (e.g., job stress) and replicate findings in diverse industrial contexts.